2012
DOI: 10.1016/j.smim.2012.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Intrathymic IL-7: The where, when, and why of IL-7 signaling during T cell development

Abstract: The thymus is the birthplace of all T lineage cells. But the thymus is also a cradle as it provides the environment for further maturation and differentiation of immature thymocytes. While many factors contribute to make the thymus a unique place for T cell development, here we review the essential role of intrathymic interleukin-7 (IL-7). In the absence of IL-7 signaling, survival, proliferation and differentiation of immature thymocytes are all severely impaired. Consequently, IL-7 is critical to nurture and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 107 publications
(142 reference statements)
1
68
0
Order By: Relevance
“…Thus, the physiological role of sγc proteins can be wide-ranging and diverse. Here we assessed the effect of sγc expression on thymic development, and we show that increased sγc production results in impaired thymopoiesis, which is a process dependent on IL-7 signaling3, and also in diminished i NKT cell generation, which is an event dependent on IL-15 signaling72139. Generation of IL-2-dependent Foxp3 + Treg cells or IL-7-dependent CD8SP thymocytes51041, on the other hand, were not affected.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, the physiological role of sγc proteins can be wide-ranging and diverse. Here we assessed the effect of sγc expression on thymic development, and we show that increased sγc production results in impaired thymopoiesis, which is a process dependent on IL-7 signaling3, and also in diminished i NKT cell generation, which is an event dependent on IL-15 signaling72139. Generation of IL-2-dependent Foxp3 + Treg cells or IL-7-dependent CD8SP thymocytes51041, on the other hand, were not affected.…”
Section: Discussionmentioning
confidence: 91%
“…Among others, IL-7 is essential for thymopoiesis23, IL-2 is necessary for Foxp3 + Treg cell development45, and IL-15 is required for the development of invariant NKT ( i NKT) cells in the thymus67. Notably, γc cytokine responsiveness is mostly acquired during or after initiation of lineage-specification during thymocyte development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, IL7 exerts a significant impact on naive T-cell survival, proliferation, and homeostasis in mammals (Hsu and Mountz, 2010; Vicente et al., 2010; Hong et al., 2012). Hsu and Mountz (2010) reported that the interaction between IL7 and IL7R could lead to proliferation and progression of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Among its pleiotropic effects, IL-7 determines the overall size of the resting T-cell pool as the prototypic survival factor for T cells. 6 In lymphoid tissues, stromal cells constitutively produce the IL-7 relevant to T-cell homeostasis, and IL-7 levels are thought to be controlled through consumption by IL-7 receptor (IL-7R)-expressing cells.…”
Section: Introductionmentioning
confidence: 99%